THE EFFECTIVENESS OF SELECTED SONGS ON SPOTIFY TO CONTINUOUS TENSES MASTERY THROUGH DEDUCTIVE APPROACH - Rahma Meisa; Ikhsanudin Ikhsanudin; Eni Rosnija (Wiralodra English Journal, 2024)
This study aims to examine the effect of selected songs on Spotify to continuous tense mastery through a deductive approach. Conducted as a quantitative research employing a pre-experimental design with one group pre-test post-test, it focused on ninth-grade students of SMP Negeri 25 Pontianak Utara in the Academic Year 2023/2024. Data collection involved a multiple-choice test comprising 12 questions, validated and deemed reliable through reliability and validity tests. Results indicated a significant enhancement in students' scores, with a pre-test mean score of 61.79 and a post-test mean score of 91.38. The t-test value of 8.508, surpassing the critical t-table value of 1.701, affirmed the alternative hypothesis. Moreover, the effect size of 1.58 signified strong effectiveness. Consequently, the study concluded that selected Spotify songs effectively facilitate continuous tense mastery through deductive methods. This research highlights opportunities for further exploration, suggesting investigation in diverse educational settings or with different student demographics to validate the efficacy of using selected songs for mastering other grammatical tenses.